2022
DOI: 10.1021/acs.est.1c03135
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Secondary Brown Carbon Produced from the Photooxidation of Naphthalene

Abstract: We investigate the chemical composition of organic light-absorbing components, also known as brown carbon (BrC) chromophores, formed in a proxy of anthropogenic secondary organic aerosol generated from the photooxidation of naphthalene (naph-SOA) in the absence and presence of NO x . Highperformance liquid chromatography equipped with a photodiode array detector and electrospray ionization high-resolution mass spectrometer is employed to characterize naph-SOA and its BrC components. We provide molecular-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 99 publications
6
51
0
Order By: Relevance
“… 78 , 79 It is positively correlated with the number of atoms in a molecule. As the NOx/VOC increases, the mean polarizability of naph -SOA increases and the density remains constant, while the MW decreases, as indicated by the significant decay of large molecules observed by Siemens et al 55 Therefore, an increase of the real part of RI is expected with the increase of the NOx/VOC ratio. At higher NOx/naphthalene ratios, the increased prevalence of NOx promotes RO 2 to react more with NOx to form nitro-organic compounds than reacting with another RO 2 to produce larger molecules (e.g., ROOR).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“… 78 , 79 It is positively correlated with the number of atoms in a molecule. As the NOx/VOC increases, the mean polarizability of naph -SOA increases and the density remains constant, while the MW decreases, as indicated by the significant decay of large molecules observed by Siemens et al 55 Therefore, an increase of the real part of RI is expected with the increase of the NOx/VOC ratio. At higher NOx/naphthalene ratios, the increased prevalence of NOx promotes RO 2 to react more with NOx to form nitro-organic compounds than reacting with another RO 2 to produce larger molecules (e.g., ROOR).…”
Section: Resultsmentioning
confidence: 88%
“…A higher nitro-organic compound content under higher NOx/naphthalene ratios was observed by HR-ToF-AMS ( Figures S3 and S4 ) and HPLC-HRMS ( Figure S7 ). Siemens et al 55 have analyzed the double-bond equivalent value (DBE) of the assigned species. They suggest that the high DBE values of the CHON compounds retain the aromaticity and are likely nitroaromatics.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high NOx emission, photooxidation of traffic VOCs may have largely involved nitrogen chemistry. Previous studies found the NOx-involved SOA could produce considerable chromophores (Lin et al, 2015;Siemens et al, 2022), such as the traffic VOCs may produce SOA in a time scale of hours, containing nitro-aromatics (Wang et al, 2019b;Keyte et al, 2016). The daytime formation of organic nitrate may follow the gas-phase photooxidation mechanism, in which the excess NO could add to the peroxy radical to produce organic nitrate (Liebmann et al, 2019).…”
Section: Simultaneous Whitening and Darkening Process Of Brcmentioning
confidence: 99%
“…11 In recent years, the sources, and optical and chemical characteristics of secondary BrC have been widely studied in eld and laboratory studies. [12][13][14][15][16] In particular, BrC produced by Maillard-like reactions between carbonyls and reduced nitrogen species (e.g., organic amines and ammonium) in clouds and aqueous aerosols has attracted increasing attention, 9,10,17,18 because the related precursors are abundant in the atmosphere and the related reactions can be greatly accelerated in atmospheric aerosols. The light-absorbing capacities of BrC formed by reactions between a series of carbonyl compounds and ammonium sulfate (AS) and/or amines were evaluated, and it is conrmed that amines are considerably more effective than AS for the production of BrC on a per mole basis.…”
Section: Introductionmentioning
confidence: 99%
“…11 In recent years, the sources, and optical and chemical characteristics of secondary BrC have been widely studied in field and laboratory studies. 12–16 In particular, BrC produced by Maillard-like reactions between carbonyls and reduced nitrogen species ( e.g. , organic amines and ammonium) in clouds and aqueous aerosols has attracted increasing attention, 9,10,17,18 because the related precursors are abundant in the atmosphere and the related reactions can be greatly accelerated in atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%